Quality Evaluation Of Locally Grown And Imported Rice In Malaysia - Tharmabalan, Rachel Thomas (2014)
In the present study, six different rice varieties marketed in Penang, Malaysia (locally grown and imported) were evaluated for proximate composition, physicochemical, cooking, functional and antioxidant properties. Among the various rice varieties investigated, 1000 kernel weight varied between 16.97-19.43 g, length/breadth (l/b) ratio was between 2.09-3.75, while bulk density varied between 0.81-0.86 g/ml. Overall, ‘Black rice’ variety had the highest protein content (8.16%) with lowest fat content (0.07%). Among the rice varieties, the total saturated and unsaturated fatty acid content was highest in black rice (5.89%). The functional and pasting properties of rice varieties showed significant difference in water absorption capacity (3.82-10.86 ml/g), oil absorption capacity (2.18-6.37 ml/g) with pH and aw varying between 6.07-6.45 and 0.62-0.68, respectively. Emulsifying activity (5.48%) and stability (98.3%), as well as foaming capacities (3.98%) were highest in glutinous rice. Significant differences were observed in pasting parameters of rice starch especially in relevance to the peak time, peak viscosity, final viscosity and setback temperature. Results also showed minimum cooking time to range between 10 to 31.67 min., and is be negatively correlated with amylose content (r = -0.97; P ≤ 0.01) with brown rice taking the longest time to cooked. Positive correlation was also recorded for both amylose content and l/b ratio in relation to elongation of cooked rice.